Understanding Contemporary Fiqh: Its Meaning and Scope in Responding to the Challenges of the Times - Erwinsyah Putra; Fera Aisah Bancin (AT-TAFAHUM: Journal of Law, 2024)
Contemporary Islamic jurisprudence (fiqh) is a branch of Islamic law that has evolved in line with the dynamics of modern life. This study aims to understand how Islamic law can respond to various new issues not explicitly discussed in classical sources. This research aims to examine the meaning of contemporary Islamic jurisprudence and its scope in responding to the challenges of the times. The method used is a library study by analyzing various literature related to Islamic jurisprudence and the development of modern Islamic law. The results of the study indicate that contemporary Islamic jurisprudence focuses not only on understanding texts but also considers the social, cultural, economic, and technological contexts developing in society. The scope of contemporary Islamic jurisprudence encompasses various aspects of life, such as sharia economics, bioethics, information technology, and social issues. With a flexible approach while remaining grounded in the Qur'an and Hadith, contemporary Islamic jurisprudence is able to provide relevant and adaptive solutions to modern problems. Therefore, a deep understanding of contemporary Islamic jurisprudence is essential for Muslims to be able to face the changing times without abandoning sharia values.